THE SCIENTIFIC AND THEORETICAL FOUNDATIONS FOR DEVELOPING THE PROFESSIONAL COMPETENCE OF FUTURE SPECIALISTS IN INFORMATION TECHNOLOGY WITHIN THE MODERN EDUCATIONAL SYSTEM (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This scientific article focuses on the measures implemented to enhance the effectiveness of vocational training and retraining systems within the information technology sector, with particular emphasis on ensuring the availability of qualified IT professionals for government agencies and network organizations. The development of professional competence in future information technology specialists is essential due to the significant role this field plays in modern society, influencing both the education system and the labor market.